The Role of Brain-Derived Neurotrophic Factor in Different Psychiatric Disorders and Neurodegenerative Diseases - Hamza, Suzan; Haddad, Namir I. A.; AL Gawwam, Gheyath (AL-Kindy College Medical Journal, 2025)
Brain-derived neurotrophic factor is a widely studied neurotrophins found throughout the mammalian central nervous system. These neurotrophins regulate numerous aspects of neuronal and oligodendroglia development and function, including axonal growth, synaptic plasticity, differentiation, proliferation, survival, and apoptosis. Brain-derived neurotrophic factors have a significant impact on neurodegenerative disorders, synaptic plasticity, and the formation and maintenance of a normal brain circuit. Precise regulation of Brain-derived neurotrophic factor concentrations, including their controlled release at the transcriptional and translational levels, is essential for the correct functioning of the central nervous system. This review provides a summary of the role of Brain-derived neurotrophic factor in various neurological and mental disorders. In addition, to its role in memory recognition by increasing neuronal proliferation and survival in the perirhinal cortex, a vital area for recognizing objects in memory.